Students evaluation of the institutional practices of selected private higher educational institutions in the cities of Las Pinas and Paranque: basis for school enhancement plan in key result areas - Sanchez-Nuyda, Ma. Socorro (Manila : National University, 2010)
The study focused on the institution's ability to meet the expectations of the fourth year college students from selected private tertiary schools in the cities of Las Pinas and Paranaque. The study was conducted towards the end of the second semester of school year 2009-2010.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Design: Descriptive Method.
Includes bibliographical references.